2018
DOI: 10.1016/j.virol.2018.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Infection by Zika viruses requires the transmembrane protein AXL, endocytosis and low pH

Abstract: The recent Zika virus (ZIKV) outbreak in Brazil has suggested associations of this virus infection with neurological disorders, including microcephaly in newborn infants and Guillian-Barré syndrome in adults. Previous reports have shown that AXL, a transmembrane receptor tyrosine kinase protein, is essential for ZIKV infection of mammalian cells, but this remains controversial. Here, we have assessed the involvement of AXL in the ability of ZIKV to infect mammalian cells, and also the requirement for endocytos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 39 publications
1
65
1
1
Order By: Relevance
“…S2). Next, we investigated the expression of the AXL receptor for ZIKV [85,86] as well as other related molecules such as CD209 [87] and TYRO3 [88]. Consistent with vertical transmission, AXL, the preferred receptor for ZIKV, was highly expressed by the cells of the human placenta and chorioamniotic membranes throughout gestation (Fig.…”
Section: Main Textmentioning
confidence: 96%
“…S2). Next, we investigated the expression of the AXL receptor for ZIKV [85,86] as well as other related molecules such as CD209 [87] and TYRO3 [88]. Consistent with vertical transmission, AXL, the preferred receptor for ZIKV, was highly expressed by the cells of the human placenta and chorioamniotic membranes throughout gestation (Fig.…”
Section: Main Textmentioning
confidence: 96%
“…This first antipsychotic medication was discovered in 1952 by Jean Delay and Pierre Deniker at Sainte Anne hospital (2). In addition to its antipsychotic activity, a growing body of in vitro studies has demonstrated antiviral properties, for example against influenza (3), hepatitis viruses (4), alphaviruses (5), JC virus (6), Japanese encephalitis virus (7), bronchitis-virus (8), MHV-2 (9), Zika virus (10) or dengue virus (11). CPZ has also been shown to have antiviral activity against coronaviruses in multiple studies (12)(13)(14).…”
mentioning
confidence: 99%
“…Bafilomycin A1 is a well-characterized inhibitor of the V-ATPase and it has been frequently used to restrain the infection of viruses internalized by receptor-mediated endocytosis. Persaud et al [30] demonstrate that this compound inhibits the entry of ZIKV MR766 strain in Vero and Cf2Th cells. Our data show that bafilomycin A1 strongly impairs the entry of ZIKV Uganda 976 (known to cause only mild symptoms) and ZIKV French Polynesia PF13/251013-18 (associated with neurological complications) in A549 and in SH-SY5Y cells.…”
Section: Discussionmentioning
confidence: 99%
“…Persaud et al [30] showed that the acidification of the endosomal compartment is crucial for the entry of the ZIKV-MR766 strain. We wondered whether this would differ between a strain responsible for only causing mild symptoms (Uganda 976) and a strain known to be associated with neurological complications (PF13/251013-18).…”
Section: Bafilomycin A1 Inhibits the Establishment Of Infection By Zikvmentioning
confidence: 99%